Negative pole piece, preparation method thereof and lithium ion battery

By adopting a multi-layer structure design in the negative electrode sheet of the lithium-ion battery, the lyophilic coating is added, the problem of uneven infiltration of the electrolyte is solved and the overall performance of the battery is improved.

CN119695160APending Publication Date: 2025-03-25JIANGSU RELIANCE ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510049639.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, the electrolyte of the negative electrode sheet is unevenly infiltrated, resulting in uneven current density distribution and safety problems, and the existing technology has not effectively solved this problem.

Method used

A multi-layer structure electrode design is adopted, and a lyophilic coating is added in the middle of the double-layer active material layer to improve the wetting uniformity of the electrolyte, optimize the current density distribution, and reduce the pore impedance of the negative electrode sheet.

Benefits of technology

By adding the lyophilic coating, the diffusion direction of the electrolyte becomes bidirectional, which improves the liquid immersion rate and wetting uniformity, reduces the pole impedance of the electrodes, and improves the comprehensive performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695160A_ABST
    Figure CN119695160A_ABST
Patent Text Reader

Abstract

The invention provides a negative pole piece, a preparation method thereof and a lithium ion battery. The negative pole piece is used in the lithium ion battery and comprises a current collector and an active material coating formed on at least one surface of the current collector. The active material coating comprises a first active material coating, a second active material coating and a lyophilic coating arranged between the first active material coating and the second active material coating. The lyophilic coating is additionally coated between the two layers of active material coatings, so that the diffusion direction of the electrolyte is changed from a single direction to bidirectional diffusion, the immersion speed is increased, the infiltration uniformity of the electrolyte in the Z-axis direction of the thick electrode plate is improved, and the comprehensive performance of the lithium ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a negative electrode plate and a preparation method thereof, and a lithium-ion battery. Background Art

[0002] Lithium-ion batteries (LIBs) have been widely used in electronic devices and are entering the electric vehicle (EV) and grid energy storage markets. The demand for higher energy density LIBs and improved performance has been growing. One of the challenging technical barriers to the development of high energy density lithium-ion batteries is to improve the utilization of electrode capacity and reduce the poor electrolyte wetting due to high electrode compaction density or excessive electrode thickness. Therefore, improving the electrolyte wettability of electrode sheets is considered to be the key to solving this problem. Uneven wetting can lead to uneven current density distribution and unstable solid electrolyte interface (SEI) formation; incomplete wetting can affect battery performance and lead to lithium plating at the negative electrode, leading to safety issues.

[0003] Related technologies include preparing lithium-ion batteries by functionally coating the diaphragm, that is, first coating the diaphragm with a composite functional slurry, and then placing the functional coated diaphragm between the negative electrode and the positive electrode. In the preparation process of coating the composite functional slurry, two layers of material are used for coating, and a wetting agent is added to the preparation of one layer of composite coating slurry. The prepared diaphragm can absorb and retain more electrolyte, thereby improving the wettability of the diaphragm. It can be seen that this technology is aimed at improving the wettability of the diaphragm, and does not explore the problem of whether the electrolyte is uniformly infiltrated. It is more about reducing the extrusion between the electrode and the diaphragm, extending the life of the diaphragm, and thus improving the charge and discharge performance of the battery. At present, no research has been found on related targeted technologies for more uniform electrolyte infiltration of the negative electrode itself. Therefore, it is urgent to provide a solution that is simpler to operate and can improve the overall performance of the battery by only improving the uniformity of the electrolyte infiltration of the negative electrode itself. Summary of the invention

[0004] Based on this, the present application provides a multi-layer structure electrode design, which increases the immersion rate, reduces the concentration gradient of the electrolyte distribution, improves the wetting uniformity of the electrolyte in the Z-axis direction of the thick electrode sheet, optimizes the current density distribution, and reduces the pore impedance of the negative electrode sheet, thereby improving the comprehensive performance of the lithium-ion battery.

[0005] The specific technical solution of this application is:

[0006] In a first aspect, the present application provides a negative electrode plate for use in a lithium-ion battery, comprising a current collector and an active material coating formed on at least one side of the current collector, wherein the active material coating comprises a first active material coating, a second active material coating, and a lyophilic coating disposed between the first active material coating and the second active material coating.

[0007] Among them, the lyophilic coating refers to a coating that is electrolyte-philic, that is, this coating has a strong affinity for the electrolyte, can quickly adsorb and maintain contact with the electrolyte, so that the coating surface is easily wetted by the electrolyte.

[0008] In some embodiments, the material of the lyophilic coating includes silicon dioxide powder, a conductive agent and a binder, the mass percentage of the conductive agent is 0.5-2.0%, and the mass percentage of the binder is 1.0-3.0%.

[0009] Wherein, the conductive agent is generally carbon nanotubes.

[0010] Wherein, the binder is generally styrene-butadiene rubber.

[0011] Preferably, the particle size D50 of the silicon dioxide powder is 200-900 nm, and more preferably 300-800 nm.

[0012] The particle size D50 generally refers to the average particle size of the silica powder material.

[0013] In the present application, by controlling the particle size D50 of the silica powder within a certain numerical range, the pores of the silica powder and the capillary channels after the coating is formed are sufficiently abundant, thereby enhancing the liquid absorption capacity and maintaining it at a high level.

[0014] In some embodiments, the silica powder may be a silica powder including a mixture of different particle sizes.

[0015] Preferably, the silicon dioxide powder includes a first type of silicon dioxide powder with a particle size of D50=300-550 nm and a second type of silicon dioxide powder with a particle size of D50=600-800 nm.

[0016] The difference between the first type of silicon dioxide powder and the second type of silicon dioxide powder is generally only in the size of the particle size D50.

[0017] Preferably, the weight percentage of the first type of silicon dioxide powder is 60-80%.

[0018] Preferably, the weight percentage of the second type of silicon dioxide powder is 20-40%.

[0019] In this application, % generally refers to weight percentage.

[0020] In some embodiments, the lyophilic coating has a thickness of 2-8 microns, such as 5-7 microns.

[0021] In some embodiments, the thickness of the first active material coating layer and the second active material coating layer are both 30-80 microns, such as 40-60 microns.

[0022] In some embodiments, the thickness of the current collector is 6-20 microns, such as 8-10 microns.

[0023] In some embodiments, the first active material coating and the second active material coating both include graphite and / or silicon, a conductive agent, and a binder, and the component raw materials of the first active material coating and the second active material coating may be the same or different.

[0024] The conductive agent is generally selected from one or more of conductive carbon black (SP), acetylene black, Ketjen black, carbon nanotubes and graphene.

[0025] The binder is generally selected from one or more of polyacrylic acid, polyvinyl alcohol, hydroxymethyl cellulose, sodium hydroxymethyl cellulose, styrene-butadiene rubber, polyethylene glycol and polyvinylidene fluoride.

[0026] In some embodiments, the current collector includes one or more of copper foil, graphite paper and copper foam, preferably copper foil.

[0027] In a second aspect, the present application provides a method for preparing the negative electrode sheet as described in the first aspect, the preparation method comprising the following steps:

[0028] S1, mixing graphite and / or silicon, a conductive agent, a binder and a solvent to obtain a slurry;

[0029] S2. Coating the slurry on at least one surface of the current collector, coating the material of the lyophilic coating on the surface of the slurry, and subsequently coating another layer of slurry on the surface of the lyophilic coating to obtain a layered negative electrode sheet.

[0030] In some embodiments, the mass ratio of the graphite and / or silicon, the conductive agent, and the binder is (48-52): (0.4-1): (0.5-1.5).

[0031] In some embodiments, in step S2, after the coating, a drying step is included.

[0032] The drying temperature may be 60-90°C.

[0033] The drying equipment generally adopts conventional heating equipment in the art, such as an oven.

[0034] In some embodiments, the solvent is generally selected from one or more of N-methylpyrrolidone, deionized water, dimethyl sulfoxide and tetrahydrofuran.

[0035] In a third aspect, the present application further provides a lithium-ion battery, which comprises the negative electrode plate, the positive electrode plate, the electrolyte and the separator as described in the first aspect.

[0036] Compared with the prior art, this application has the following advantages:

[0037] (1) The present application proposes a novel multi-layer structured negative electrode sheet. By adding a lyophilic coating layer between the double-layer active material coating, the diffusion direction of the electrolyte is changed from a single direction to a bidirectional diffusion, thereby increasing the rate of immersion and improving the uniformity of electrolyte infiltration in the Z-axis direction of the thick electrode sheet. At the same time, the current density distribution is optimized, and the pore impedance of the negative electrode sheet is reduced, thereby improving the overall performance of the lithium-ion battery.

[0038] (2) The present application further selects silica powder as the material of the lyophilic coating, which has abundant pores and strong liquid absorption capacity. By setting the particle size and thickness that meet the conditions, the particles are arranged regularly. The synergistic effect of the particle pores and multi-level channels can increase the liquid absorption rate, thereby reducing the electrode hole impedance. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the technical solution of the present application, the drawings required for use in the description of the present application will be briefly introduced below.

[0040] Figure 1 It is a schematic diagram of the structure of the negative electrode plate and the separator in the specific implementation method of the embodiment of the present application. DETAILED DESCRIPTION

[0041] Examples of the present embodiment are described in detail below. The examples are only used to explain the present embodiment and are not to be construed as limiting the present embodiment.

[0042] In the description of this embodiment, if there are descriptions of first, second, first category, second category, etc., they are only used for the purpose of distinguishing technical features and cannot be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features or implicitly indicating the sequence of the indicated technical features.

[0043] In this document, "and / or" means either or both.

[0044] In the description of the embodiments of the present application, it should be noted that all ranges disclosed in the present application will be understood to include any and all sub-ranges included therein. For example, the stated range "30-60 microns" should be deemed to include any and all sub-ranges as follows: it starts with a minimum value of 30 or greater and ends with a maximum value of 60 or less, for example, 30 to 40 microns, or 45 to 60 microns, or 40 to 50 microns. At the same time, all ranges disclosed in the present application are also deemed to include the endpoints of the ranges, unless otherwise explicitly stated. For example, the range "between 6 and 20" or "6 to 20" or "6-20" should generally be deemed to include the endpoints 6 and 20.

[0045] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0046] The present application is a multi-layer structure electrode design proposed to improve the problem of electrolyte wetting uniformity in the Z-axis direction of thick electrode sheets. The inventors found that forming a lyophilic coating between two layers of active material can effectively accelerate the diffusion of the electrolyte and improve the wettability of the thick electrode.

[0047] By adding a layer of lyophilic coating in the middle of the double-layer active material coating, the diffusion direction of the electrolyte is changed from a single direction to a bidirectional diffusion, the immersion rate is increased, and the wetting uniformity of the electrolyte in the Z-axis direction of the thick electrode sheet is improved; at the same time, the current density distribution is optimized, and the pore impedance of the negative electrode sheet is reduced, thereby improving the comprehensive performance of the lithium-ion battery.

[0048] The negative electrode plate provided in the present application is used in a lithium-ion battery, and includes a current collector and an active material coating formed on the current collector, wherein the active material coating includes a first active material coating, a second active material coating, and a lyophilic coating arranged between the first active material coating and the second active material coating.

[0049] In the present application, the reason why the above-mentioned structure can improve the wetting uniformity of the electrolyte in the electrode is that the lyophilic coating has a stronger affinity with the electrolyte than the active material coating of the negative electrode. When reacting with the electrolyte, it first undergoes physical adsorption with the electrolyte. At the same time, after thickness optimization, the lyophilic coating has abundant pores and capillaries, which further improves the overall coating's liquid absorption rate and the homogeneity of the wetting, and the granular electrolyte is fully contacted and infiltrated, thereby reducing the electrode hole impedance.

[0050] In some embodiments, the material of the lyophilic coating includes silicon dioxide powder, a conductive agent and a binder, the mass percentage of the conductive agent is 0.5-2.0%, and the mass percentage of the binder is 1.0-3.0%.

[0051] The conductive agent and the binder are generally conventionally selected in the art. The conductive agent is carbon nanotubes, and the binder is styrene-butadiene rubber.

[0052] In the present application, the particle size D50 of the silica powder is further screened and controlled at a certain value so that the pores of the silica powder and the capillary channels after the coating are formed are sufficiently rich, thereby enhancing the liquid absorption capacity and maintaining it at a high level.

[0053] In some embodiments, the particle size D50 of the silicon dioxide powder is 200-900 nm, preferably 300-800 nm.

[0054] In some embodiments, the thickness of the lyophilic coating is 2-8 microns, preferably 5-7 microns.

[0055] In the present application, if the thickness of the lyophilic coating is too thin, the electrode absorption improvement effect will be average due to the small liquid absorption pores; if the thickness is too thick, although the electrode absorption rate will be improved, the increase in load will lead to an increase in the electrode hole impedance, which is not conducive to improving the system effect.

[0056] In the present application, in particular, silica powder is selected as the material of the lyophilic coating, which has abundant pores and strong liquid absorption capacity. By setting the particle size and thickness that meet the conditions, the particles are arranged regularly. The synergistic effect of the particle pores and multi-level channels can increase the liquid absorption rate, thereby reducing the electrode hole impedance.

[0057] In some embodiments, the silicon dioxide powder may be a mixture of silicon dioxide powders having different particle sizes.

[0058] In some embodiments, the silica powder includes a first type of silica powder having a particle size of D50=300-550 nm and a second type of silica powder having a particle size of D50=600-800 nm.

[0059] Preferably, the weight percentage of the first type of silicon dioxide powder is 60-80%, such as 70-80%.

[0060] Preferably, the weight percentage of the second type of silicon dioxide powder is 20-40%, such as 20-30%.

[0061] In some embodiments, the silicon dioxide powder includes a first type of silicon dioxide powder with a particle size D50=300-550 nm, and a weight percentage of 60-80%.

[0062] In some embodiments, the silicon dioxide powder includes a second type of silicon dioxide powder with a particle size D50=600-800 nm, accounting for 20-40% by weight.

[0063] In the present application, when mixed silica powders with different particle sizes are used, the comprehensive pore area and the number of pores are increased, further improving the liquid absorption rate, and the particles are fully contacted and infiltrated by the electrolyte, thereby reducing the electrode hole impedance.

[0064] In some embodiments, the silicon dioxide powder includes a first type of silicon dioxide powder having a particle size of D50=350-450 nm and a second type of silicon dioxide powder having a particle size of D50=700-800 nm.

[0065] In some embodiments, the silicon dioxide powder includes a first type of silicon dioxide powder with a weight percentage of 60-80% and a particle size D50=400nm, and a second type of silicon dioxide powder with a weight percentage of 20-40% and a particle size D50=750nm.

[0066] In some embodiments, the silicon dioxide powder includes a first type of silicon dioxide powder with a weight percentage of 70% and a particle size D50=400 nm, and a second type of silicon dioxide powder with a weight percentage of 30% and a particle size D50=750 nm.

[0067] In the present application, when the particle size D50 of the first type of silica powder and the second type of silica powder are 400nm and 750nm respectively, and the weight ratio is 7:3, the pore continuity and capillary permeability formed by the mixture of particles of the two particle sizes reach the optimal level, so that the transmission speed of the electrolyte in the pores is accelerated. At the same time, the particles are fully infiltrated by the electrolyte, the concentration polarization is reduced, and the electrode hole impedance is reduced.

[0068] In some embodiments, the raw materials of the first active material coating layer and the second active material coating layer are generally conventional electrode active materials in the art, and may be the same or different.

[0069] In some embodiments, the first active material coating layer and the second active material coating layer may generally include graphite and / or silicon, a conductive agent, and a binder.

[0070] Among them, the conductive agent and the binder can be conventionally selected in the art. In some embodiments, the conductive agent can be one or more of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes and graphene; the binder can be one or more of polyacrylic acid, polyvinyl alcohol, hydroxymethyl cellulose, sodium hydroxymethyl cellulose, styrene-butadiene rubber, polyethylene glycol and polyvinylidene fluoride.

[0071] In some embodiments, the negative electrode coating is divided into a first active material coating, a lyophilic coating, and a second active material coating in a direction away from the surface of the current collector.

[0072] Figure 1 is a schematic diagram of the structure of the negative electrode plate and the diaphragm in the specific implementation mode of the present application, showing the infiltration of the electrolyte into the electrode plate. Figure 1 It can be seen that the grayscale depth of the multi-layer negative electrode is consistent, indicating that the electrolyte has evenly infiltrated the electrode. This is because a lyophilic coating is added between the first active material coating and the second active material coating, which changes the diffusion direction of the electrolyte from a single direction to a bidirectional diffusion, making the infiltration more complete.

[0073] In some embodiments, the method for preparing the negative electrode sheet comprises the following steps:

[0074] S1, mixing graphite and / or silicon, a conductive agent, a binder and a solvent to obtain a slurry;

[0075] S2, coating the material of the lyophilic coating on at least one surface of the current collector, coating the material of the lyophilic coating on the surface of the slurry, and subsequently coating another layer of slurry on the surface of the lyophilic coating to obtain a layered negative electrode sheet.

[0076] Wherein, the conductive agent and the adhesive are both the conductive agent and the adhesive mentioned above.

[0077] The solvent is conventional in the art, and can generally be selected from one or more of N-methylpyrrolidone, deionized water, dimethyl sulfoxide and tetrahydrofuran, preferably deionized water.

[0078] In some embodiments, in step S2, a drying step is included after the coating, and the drying temperature is 60-100°C, for example, 80°C.

[0079] The coating includes coating the slurry on at least one surface of the current collector, coating the material of the lyophilic coating on the surface of the slurry, and coating another layer of slurry on the surface of the lyophilic coating.

[0080] The slurry coated on at least one surface of the current collector and the subsequent coating of another layer of slurry on the surface of the lyophilic coating layer can be a first negative electrode slurry obtained by mixing and slurrying the same type of graphite and / or silicon, conductive agent, binder and solvent, or can be a first negative electrode slurry and a second negative electrode slurry respectively obtained by mixing and slurrying different types of graphite and / or silicon, conductive agent, binder and solvent; but regardless of whether they are the same slurry or not, both will form a double-layer negative electrode plate, and a layer of lyophilic coating will be added between such a double-layer structure.

[0081] In some embodiments, the mass ratio of the graphite and / or silicon, the conductive agent, and the binder may be conventional in the art, generally (48-52): (0.4-1): (0.5-1.5).

[0082] In some embodiments, the lithium-ion battery is composed of the aforementioned negative electrode sheet, positive electrode sheet, electrolyte and separator.

[0083] The electrolyte and electrolyte solvent may be conventional electrolytes and electrolyte solvents used in lithium-ion batteries, such as a mixed solvent of EC:DMC with a mass ratio of 1:1, and an electrolyte containing 1.0M LiPF6 in the mixed solvent.

[0084] The present application is further explained below with reference to embodiments.

[0085] The materials involved in the examples and comparative examples of the present application are commercially available. Silica powder with a particle size of D50 = 750 nm can be purchased from Xi'an Qiyue Biology, and silica powder with a particle size of D50 = 400 nm can be purchased from McLean. The molecular weight of polymethyl methacrylate powder is 15,000, CAS No. 9011-14-7, and the particle size D50 is 400 nm; the molecular weight of polystyrene-butyl acrylate powder is 40,000, CAS No. 25586-20-3, and the particle size D50 is 400 nm; the molecular weight of polyurethane powder is 50,000, CAS No. 51852-81-4, and the particle size D50 is 400 nm.

[0086] Example 1

[0087] Embodiment 1 of the present application provides a negative electrode plate, and the negative electrode plate is prepared by the following steps:

[0088] S1: Graphite, conductive carbon black, sodium hydroxymethyl cellulose, styrene-butadiene rubber and water are homogenized in a mass ratio of 50:0.5:0.5:0.4:50 to obtain slurry 1, which is evenly coated on a copper foil with a thickness of 8 μm by a coater, and dried in an oven at 80°C to a coating thickness of 50 μm to obtain a pole piece 1;

[0089] S2: Then, a layer of lyophilic coating is applied on at least one surface of the pole piece 1. The material of the lyophilic coating includes silicon dioxide powder with a particle size D50=400nm, 1% by weight of carbon nanotubes as a conductive agent, and 1.5% by weight of styrene-butadiene rubber as a binder. After drying in an oven at 80°C, the total thickness of the coating is 55 microns.

[0090] S3: Next, a layer of slurry 1 is continuously coated on the electrode 1 coated with silicon dioxide powder. After drying in an oven at 80° C., the total thickness of the coating is 105 μm.

[0091] Example 2

[0092] Embodiment 2 provides a negative electrode plate, which differs from Embodiment 1 in that the silica powder in the material of the lyophilic coating in step S2 is a silica powder mixed with two particle sizes, the first type of silica powder has a particle size D50 = 400nm, and the weight percentage of the mixed particle size is 50%, and the second type of silica powder has a particle size D50 = 750nm, and the weight percentage of the mixed particle size is 50%.

[0093] Example 3

[0094] Embodiment 3 provides a negative electrode plate, which differs from Embodiment 1 in that the silica powder in the material of the lyophilic coating in step S2 is a silica powder mixed with two particle sizes, the first type of silica powder has a particle size D50 = 400nm, and the weight percentage of the mixed particle size is 30%, and the second type of silica powder has a particle size D50 = 750nm, and the weight percentage of the mixed particle size is 70%.

[0095] Example 4

[0096] Embodiment 4 provides a negative electrode plate, which differs from Embodiment 1 in that the silica powder in the material of the lyophilic coating in step S2 is a silica powder mixed with two particle sizes, the first type of silica powder has a particle size D50 = 400nm, and the weight percentage of the mixed particle size is 70%, and the second type of silica powder has a particle size D50 = 750nm, and the weight percentage of the mixed particle size is 30%.

[0097] Example 5

[0098] Example 5 provides a negative electrode plate, which differs from Example 1 in that the total thickness of the coating after drying in an oven at 80° C. in step S2 is 52 μm.

[0099] Example 6

[0100] Example 6 provides a negative electrode plate, which differs from Example 1 in that the total thickness of the coating after drying in an oven at 80° C. in step S2 is 58 μm.

[0101] Example 7

[0102] Example 7 provides a negative electrode plate, which differs from Example 1 in that the particle size D50 of the silicon dioxide powder in step S2 is 200 nm.

[0103] Example 8

[0104] Embodiment 8 provides a negative electrode plate, which differs from Embodiment 1 in that the particle size D50 of the silicon dioxide powder in step S2 is 900 nm.

[0105] Comparative Example 1

[0106] Comparative Example 1 provides a negative electrode plate, which differs from Example 1 in that the silicon dioxide powder in step S2 is replaced by polymethyl methacrylate powder.

[0107] Comparative Example 2

[0108] Comparative Example 2 provides a negative electrode plate, which differs from Example 1 in that the silicon dioxide powder in step S2 is replaced by polystyrene-butyl acrylate powder.

[0109] Comparative Example 3

[0110] Comparative Example 3 provides a negative electrode plate, which differs from Example 1 in that the silicon dioxide powder in step S2 is replaced by polyurethane powder.

[0111] Comparative Example 4

[0112] Comparative Example 4 provides a negative electrode sheet, which is prepared by the following steps:

[0113] S: Graphite, conductive carbon black, sodium hydroxymethyl cellulose, styrene-butadiene rubber and water are homogenized in a mass ratio of 50:0.5:0.5:0.4:50 to obtain slurry 1, which is evenly coated on a copper foil with a thickness of 8 μm by a coater, and dried in an oven at 80°C to a coating thickness of 50 μm to obtain a pole piece 1;

[0114] S2: Then, a layer of slurry 1 is continuously coated on the pole piece 1, and after drying in an oven at 80°C, the coating thickness is 55 μm in total;

[0115] S3: Next, a layer of slurry 1 is applied on the electrode 1 coated with a layer of slurry 1. After drying in an oven at 80°C, the total thickness of the coating is 105 μm.

[0116] The specific parameters of the above examples and comparative examples are shown in Tables 1 and 2 below:

[0117] Table 1

[0118]

[0119] Table 2

[0120]

[0121]

[0122] Performance Evaluation

[0123] Test 1: Liquid absorption rate test method

[0124] Cut the negative electrode into 15cm*4cm pieces and weigh them as m1(g). Place the electrode on the inner wall of a 200mL beaker containing 50mL of electrolyte (1.0M LiPF6 in a mixed solvent of EC:DMC with a mass ratio of 1:1). Keep the electrode vertically and slowly lower it to 1cm below the liquid surface. Start timing. When the liquid rises to the 12cm mark, stop timing and record it as t(min). The weighed mass is m2(g). The liquid absorption rate is calculated as: (m2-m1) / t(g / min). Repeat the test 3 times and take the average value.

[0125] Test 2: Pole hole impedance test method

[0126] The electrode was cut into 6 small pieces of 6cm*5cm by a mold, the coating in the ear area was scraped off and wiped clean, and then the ear was welded. A layer of diaphragm (12 microns thick) was added between each two small electrode pieces, and then packaged in an aluminum-plastic film, and 0.3g of electrolyte (1.0M LiPF6 in a mixed solvent of EC:DMC with a mass ratio of 1:1) was injected to assemble into 3 symmetrical batteries; the EIS pore impedance spectrum of the symmetrical battery at 25±2℃ was tested by an electrochemical workstation, and the pore impedance of the electrode (in mΩ.cm) was measured by the 45o angle oblique part in the high and medium frequency region. 2 ), taking the average value of 3 symmetrical batteries.

[0127] The results of tests one and two are shown in Table 3.

[0128] Table 3

[0129]

[0130] It can be seen from the data in the table that from the comparison of the effects of Example 1 and Comparative Example 4, and Comparative Examples 1-3 and Comparative Example 4, it can be seen that when the electrode includes a lyophilic coating, the liquid absorption rate of the electrode is improved, the electrode hole impedance is reduced, and the uniformity of the electrolyte infiltration is improved to a certain extent, and the performance of the lithium-ion battery is improved.

[0131] By comparing the effects of Example 1 and Comparative Examples 1-3, it can be seen that when the raw material of the lyophilic coating is silica powder, the liquid absorption rate of the electrode is relatively higher and the pore impedance of the electrode is relatively lower, indicating that by using silica powder as the raw material for the lyophilic coating of the negative electrode of the multi-layer structure, the uniformity of the electrolyte infiltration is improved to a certain extent, thereby improving the battery performance of the electrode.

[0132] From the comparison of the effects of Example 1 and Examples 7-8, it can be seen that when the lyophilic coating uses silica powder with a particle size D50 of 300-800nm, the liquid absorption rate of the electrode is higher than when the particle size of the silica powder is D50 = 200nm or 900nm, and the pore impedance of the electrode is lower than when the particle size is D50 = 200nm or 900nm.

[0133] From the comparison of the effects of Example 1 and Examples 5-6, it can be seen that when the thickness of the lyophilic coating is 5 microns, the liquid absorption rate of the electrode is higher and the hole impedance of the electrode is lower than when the thickness of the lyophilic coating is 2 microns and 8 microns. However, the effect of the electrode when the thickness of the lyophilic coating is 2 microns and 8 microns is better than that of the control example.

[0134] From the comparison of the effects of Examples 2-4, it can be seen that when the first type of silicon dioxide powder with a particle size of D50 = 300-550nm accounts for 60-80% in the lyophilic coating, and the second type of silicon dioxide powder with a particle size of D50 = 600-800nm ​​accounts for 20-40%, the liquid absorption rate of the pole piece is relatively higher and the pore impedance of the pole piece is relatively lower. This shows that at this time, the uniformity of electrolyte infiltration is relatively higher and the battery performance of the pole piece is better.

[0135] Although examples of the present embodiment have been shown and described, those skilled in the art will appreciate that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present embodiment, and the scope of the present embodiment is defined by the claims and their equivalents.

Claims

1. A negative electrode plate for use in a lithium-ion battery, comprising a current collector and an active material coating formed on at least one side of the current collector, characterized in that: The active material coating layer includes: a first active material coating layer, a second active material coating layer, and a lyophilic coating layer disposed between the first active material coating layer and the second active material coating layer.

2. The negative electrode sheet according to claim 1, characterized in that: The material of the liquid-philic coating comprises silicon dioxide powder, a conductive agent and a binder. The mass percentage of the conductive agent is 0.5-2.0%, and the mass percentage of the binder is 1.0-3.0%.

3. The negative electrode sheet according to claim 2, characterized in that: The particle size D50 of the silicon dioxide powder is 300-800 nm.

4. The negative electrode sheet according to claim 3, characterized in that: The silicon dioxide powder includes a first type of silicon dioxide powder with a particle size of D50=300-550 nm and a second type of silicon dioxide powder with a particle size of D50=600-800 nm.

5. The negative electrode sheet according to claim 4, characterized in that: The weight percentage of the first type of silicon dioxide powder is 60-80%. And / or, the weight percentage of the second type of silicon dioxide powder is 20-40%.

6. The negative electrode sheet according to any one of claims 2 to 5, characterized in that: The conductive agent is carbon nanotube, and / or the binder is styrene-butadiene rubber.

7. The negative electrode sheet according to any one of claims 1 to 5, characterized in that: Meet one or more of the following conditions: a. The thickness of the lyophilic coating is 2-8 microns; b. The thickness of the first active material coating is 30-80 microns; c. The thickness of the second active material coating is 30-80 microns; d. The thickness of the current collector is 6-20 microns.

8. The negative electrode sheet according to any one of claims 1 to 5, characterized in that: The first active material coating and the second active material coating both include graphite and / or silicon, a conductive agent, and a binder, and the component raw materials of the first active material coating and the second active material coating are the same or different; And / or, the current collector comprises one or more of copper foil, graphite paper and copper foam, preferably copper foil.

9. The negative electrode sheet according to claim 8, characterized in that: Meet one or more of the following conditions: a. The conductive agent is selected from one or more of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes and graphene; b. The binder is selected from one or more of polyacrylic acid, polyvinyl alcohol, hydroxymethyl cellulose, sodium hydroxymethyl cellulose, styrene-butadiene rubber, polyethylene glycol and polyvinylidene fluoride.

10. A method for preparing a negative electrode sheet according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, mixing graphite and / or silicon, a conductive agent, a binder and a solvent to obtain a slurry; S2. Coating the slurry on at least one surface of the current collector, coating the material of the lyophilic coating on the surface of the slurry, and subsequently coating another layer of slurry on the surface of the lyophilic coating to obtain a layered negative electrode sheet.

11. The method for preparing a negative electrode sheet according to claim 10, characterized in that: Meet one or more of the following conditions: a. The mass ratio of the graphite and / or silicon, the conductive agent and the binder is (48-52): (0.4-1): (0.5-1.5); b. In step S2, the coating step includes a drying step, and preferably, the drying temperature is 60-90° C.; c. The solvent is selected from one or more of N-methylpyrrolidone, deionized water, dimethyl sulfoxide and tetrahydrofuran.

12. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode sheet, the positive electrode sheet, the electrolyte and the separator as described in any one of claims 1 to 9.